Answer:
D h(x) = f(x)×g(x)
Step-by-step explanation:
h(x) has a wave with 2 changes in direction.
so, this needs to be an expression of the third degree (there must be a term with x³ as the highest power of x).
and that is only possible when multiplying both basic functions. all the other options would keep it at second degree (x²) or render it even to a first degree (linear).
First it is important to notice that the b is 6, h is 8 and l is? so we find l by using the trigonometry which gives us approximately 13, then we plug it in to V= 1/2 lbh= 1/2 (6)(8)(13)= 312 cm^3
Answer:
(2)
Step-by-step explanation:
Let f(x) = y → f-¹(x) = f(y) = x, f(y) is the inverse of f(x)
Thus,
=> -x³ - 9 = y
=> - y - 9 = x³
=> (-y - 9)^(1/3) = x
=> f(y) = x
Inverse is (-y-9)^(1/3)
Replacing the variable, inverse is (-x-9)^(1/3)
Option (2)
Area of a square:
(x-2)(x-2)
=(x-2)^2
=x^2-2x-2x+4
=x^2-4x+4 unit sq
3+n/6
sum is adding so
3+
and the quotient (so division)
n (divided by)6
n/6
3+n/6